Artificial peptides for antitumoral siRNA delivery. Issue 10 (24th February 2020) - Luo, Jie; Wagner, Ernst; Wang, Yanfang
Abstract : Assembly of artificial amino acids into sequence-defined oligoaminoamides generates siRNA nanoplex or lipopolyplex carriers for tumor-directed gene silencing. Abstract : Intracellular delivery has been critical for the success of siRNA and related therapeutic nucleic acids. Improvement of delivery carriers will positively influence the efficacy of future nanomedicines. Our strategy for optimizing siRNA nanocarriers focuses on a bioinspired sequence-defined process including (i) identification of artificial amino acids active in specific delivery steps, (ii) assembly into defined sequences by solid phase-assisted synthesis (SPS), and (iii) screening for siRNA delivery, selection of top candidates and understanding structure–activity relations, followed by (iv) sequence variation for the next round of carrier selection. In the current review, our experience with this artificial peptide evolution in tumor-directed siRNA delivery is addressed. The medium-sized oligoaminoamides show better biological compatibility and can be functionalized to meet the requirements of siRNA delivery, such as formation of stable nanoparticles, shielding against proteins in the bloodstream, targeting into tumor tissue, and intracellular siRNA release in bioactive form.